Agronomic Biofortification of Significant Cereal Crops with Selenium—A Review - Lucija Galić; Tomislav Vinković; Boris Ravnjak; Zdenko Lončarić (Agronomy, 2021)
Selenium (Se) is an important micronutrient which is essential for most living organisms and occurs in both organic and inorganic forms in the water system, soils, biomass, and the atmosphere. In addition to being essential for humans and animals, Se is beneficial for plants and is mostly involved in antioxidant activity/response, as well as a growth promoter. Se deficiency in the diet is a global problem, and Se levels in soils generally reflect its presence in food and, thus, availability to humans. Se participates in the antioxidant response mechanisms of the organism, heavy-metal detoxification, and regulation of the reproductive and immune system, as well as ensures the proper function of the thyroid gland. Plants are the main dietary source of Se for humans. Biofortification is a key strategy to increase Se in edible parts of plants. Agronomic biofortification provides an effective route to increase Se content in edible crop products via application of Se-enriched fertilizers to soil or by foliar application. The most common cereals in the human diet are wheat, rice, maize, and barley, making them the most suitable targets for agronomic biofortification. This review focuses on summarizing the most efficient form and method of Se application via agronomic biofortification corroborated by a meta-analysis of the literature reports. In the assessed literature, foliar application showed better results compared to application in soil. The selenate form appears to be the more efficient form of Se for biofortification than selenite in the most common cereals in human diet: wheat, rice, maize, and barley.